The management information disclosure through a website: empirical evidence by European municipalities. (2016) - Gesuele, Benedetta; Alvino, Federico
This study examines theoretically and empirically the determinants of e-disclosure. Following a comparative-international perspective, the research aims are: to construct an e-disclosure index, based on websites contents in order to measure municipalities' transparency concerning on management information, to analyse which factors potentially determine e-disclosure levels and to explain different degrees of municipal transparency. The analysis is carried out on a set of Italian and Spanish municipalities, chosen in a casual way, during 2013. The findings show that size and leverage are management information disclosure determinants both for Italy and for Spain, the geographical position is management information disclosure determinant only for Italy.